Rotavirus surveillance system evaluation, Kilifi Hospital, Kenya - Ednah Salat; Maria Nunga; Ahmed Abade; Emmanuel Okunga (Journal of Interventional Epidemiology and Public Health)
Introduction: Rotavirus is one of the causes of acute diarrhea among children under five years. Diarrhea causes 9·9% of the 6·9 million deaths worldwide among children in this age group. The rotavirus surveillance system is aimed at determining the disease burden, and epidemiology of the virus, and monitoring the impact of vaccination. The rotavirus surveillance system was piloted at Kilifi County Hospital, Kenya in 2009 and has been active to date. The system at this site has never been evaluated. We sought to evaluate its performance.